Demokrasi di Negara Muslim: Akomodasi Unsur-unsur Kesamaan - Sirojuddin Aly (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, Jakarta, 2007)
This writing attempts to uncover the common ground between the West and Islam in one concept that each possesses, democracy and shura. Both are different concepts of statehood, as democracy comes from the Western tradition that has become an ideology whose values are relative as it is not based on revelation. The main characteristic of democracy is decisions supported by the majority vote. On the other hand, shura is derived from revelation (the Qur'an and hadith), so its values are absolute (as long as it concerns principles). The common ground between the two lies in their emphasis on consultation in resolving matters that involve the public.